Effect of passive stretching on the immobilized soleus muscle fiber morphology - Coutinho,E.L. (2004)
The aim of the present study was to determine the effect of stretching applied every 3 days to the soleus muscle immobilized in the shortened position on muscle fiber morphology. Eighteen 16-week-old Wistar rats were used and divided into three groups of 6 animals each: a) the left soleus muscle was immobilized in the shortened position for 3 weeks; b) during immobilization, the soleus was stretched for 40 min every 3 days; c) the non-immobilized soleus was only stretched. Left and right soleus muscles were examined. One portion of the soleus was frozen for histology and muscle fiber area evaluation, while the other portion was used to identify the number and length of serial sarcomeres. Immobilized muscles (group A) showed a significant decrease in weight (44 ± 6%), length (19 ± 7%), serial sarcomere number (23 ± 15%), and fiber area (37 ± 31%) compared to the contralateral muscles (P < 0.05, paired Student t-test). The immobilized and stretched soleus (group B) showed a similar reduction but milder muscle fiber atrophy compared to the only immobilized group (22 ± 40 vs 37 ± 31%, respectively; P < 0.001, ANOVA test). Muscles submitted only to stretching (group C) significantly increased the length (5 ± 2%), serial sarcomere number (4 ± 4%), and fiber area (16 ± 44%) compared to the contralateral muscles (P < 0.05, paired Student t-test). In conclusion, stretching applied every 3 days to immobilized muscles did not prevent the muscle shortening, but reduced muscle atrophy. Stretching sessions induced hypertrophic effects in the control muscles. These results support the use of muscle stretching in sports and rehabilitation.